Plant Juice Catalysed Synthesis of Substituted Pyrrole through Paal Knorr Reaction - Anis Ahmed Sheikh; Ummul Khair Asema; Abdul Ahad (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The current research work proposed the novel methodology for the synthesis of N-substituted pyrrole catalysed by juice of Kalanchoe Pinnata plant leaves. The reaction was carried out between hexan 2,5 dione and aniline. This protocol is environmentally benign cost effective and fruitful which has produced the desired product in short reaction time and easy work up. The synthesised compounds has been confirmed by 1HNMR , IR and C13 spectroscopy. The natural abundance, cost effective, non toxic and good to excellent yields are some specific features of this catalyst.